A review of the genus Reticulolaelaps Costa and redescription of R. elsae (Joharchi, Babaeian & Jalalizand) comb. nov. - Alireza Nemati; Arsalan Khalili-Moghadam; Dariusz J. Gwiazdowicz (Persian Journal of Acarology)
Our precise observations on Laelaspisella elsae Joharchi, Babaeian & Jalalizand revealed the genus misidentification. We clarify the genus placement, transfer it to Reticulolaelaps Costa and redescribe it paying attention to some discrepancies in the original description. A new definition and diagnosis of Reticulolaelaps and a key for separation of all known species of this genus are proposed. New information on female morphological characters of Reticulolaelaps faini Costa, 1968 is presented, based on specimens collected from soil in Khuzestan and Chaharmahal va Bakhtiari provinces, Iran. Pseudoparasitus lativentris (Karg) and P. jilinensis Ma are transferred from this genus to Reticulolaelaps. A new definition of the genus Pseudoparasitus is proposed.